Suitable fusion of N-terminal heptad repeats to achieve covalently stabilized potent N-peptide inhibitors of HIV-1 infection. Issue 4 (15th February 2020) - Lai, Wenqing; Wang, Chao; Yan, Jun; Liu, Huanliang; Zhang, Wei; Lin, Bencheng; Xi, Zhuge
Graphical abstract: Abstract: N-terminal heptad repeat (NHR)-derived peptide (N-peptide) fusion inhibitors, which are derived from human immunodeficiency virus (HIV) envelope glycoprotein 41 (gp41), are limited by aggregation and unstable trimer conformation. However, they could function as potent inhibitors of viral infection by forming a coiled-coil structure covalently stabilized by interchain disulfide bonds. We previously synthesized N-peptides with potent anti-HIV-1 activity and high stability by coiled-coil fusion and covalent stabilization. Here, we attempted to study the effects of NHRs of chimeric N-peptides by fusing de novo coiled-coil isopeptide bridge-tethered T21 peptides of different NHR lengths. Peptides (T21N23)3 and (T21N36)3 was a more potent HIV-1 fusion inhibitor than (T21N17)3 . The site of isopeptide bond formation was precisely controlled and had little influence on N-peptide properties. The N-peptide (T21N36)3, which had a similar conformation as the NHR trimer and interacted well with the C34 peptide, may be useful for screening other C-peptides and small-molecule fusion inhibitors, and for studying the interactions between the NHR trimer and C-terminal heptad repeats.